THE PROBLEM OF LIBERTY IN A DEMOCRACY: THE ASPECT OF COURAGE - Karalius, Gintas (Politologija, 2013)
The object of the study was to introduce an innovative approach to the long-lasting theoretical discussion about the meaning and extent of political liberty in a modern democratic society. Our suggested way to explain why the democratic political order as such might give rise to considerable challenges for political liberty introduces the classical virtue of courage as a possible key explanatory factor underlying the major tensions that emerge between democracy and liberty. Such approach provides some new insights into the debate about the origins, limits, and political perspectives of modern democracies. The analysis starts by conceptualizing modern democracy as a political form which expresses a specific ethical idea about the natural equality of people. Generally, it means that egalitarianism is the founding idea and moral purpose of a democratic political system, which tends to develop into a modern type of representative government and civil society. The second part of our analysis emphasizes the fact that liberty is by nature a political fact achieved only by practical participation of an individual in public life, and which cannot be reduced to formal, legal, economic or moral categories. Liberty, being a principle of public action, requires the capacity of a person to risk his personal wealth and safety for the sake of the common good. The third part of the analysis explains the crucial importance of the virtue of courage to the whole political life, as it is an ethical idea which aims at building such a character of a person that is capable and motivated to live an active public life. It is the virtue of courage that makes an individual morally fit and eager to practice liberty, as well as ready to defend it against any acts of despotism. Finally, the analysis assesses the diminishing role of courage due to the egalitarian public order of a democracy, resulting in adverse effects on liberty. The conclusions of the article highlight several points which are noted below. In a democratic society, courage loses its status as a virtue; thus, individuals become less capable and less motivated to live an active public life. Democracy rests on the principle that implies establishing and protecting the equality of its citizens, while the virtue of courage expresses an implicit distaste for egalitarianism and encourages people to strive for an ethically superior status than that of all the rest, i.e. it makes a clear hierarchical distinction between cowards, conformists, and heroes. That’s why democracy banishes courage from its equality favouring public life, depriving it of its ethical status. The decline of this virtue makes the practice of liberty more complicated as individuals lose interest in risking their private wealth and safety for the sake of the common good. The diminishing capacity and interest of citizens in democracy to live an active public life, while giving preference to social equality which requires no personal effort, is a major problem for political liberty. As people become indifferent to the pursuit of the common good, liberty becomes inactive, and the political community becomes less immune to various manifestations of despotism.